The PHD transcription factor ThPHD5 regulates antioxidant enzyme activity to increase salt tolerance in Tamarix hispida - Tan, Yao-Shuo (Plant science : an international journal of experimental plant biology, 2025)
Copyright © 2024 Elsevier B.V. All rights reserved.